Sulfated Glycans and Related Digestive Enzymes in the Zika Virus Infectivity: Potential Mechanisms of Virus-Host Interaction and Perspectives in Drug Discovery - Pomin, Vitor H. (Interdisciplinary Perspectives on Infectious Diseases, 2017)
As broadly reported, there is an ongoing Zika virus (ZIKV) outbreak in countries of Latin America. Recent findings have demonstrated that ZIKV causes severe defects on the neural development in fetuses in utero and newborns. Very little is known about the molecular mechanisms involved in the ZIKV infectivity. Potential therapeutic agents are also under investigation. In this report, the possible mechanisms of action played by glycosaminoglycans (GAGs) displayed at the surface proteoglycans of host cells, and likely in charge of interactions with surface proteins of the ZIKV, are highlighted. As is common for the most viruses, these sulfated glycans serve as receptors for virus attachment onto the host cells and consequential entry during infection. The applications of (1) exogenous sulfated glycans of different origins and chemical structures capable of competing with the virus attachment receptors (supposedly GAGs) and (2) GAG-degrading enzymes able to digest the virus attachment receptors on the cells may be therapeutically beneficial as anti-ZIKV. This communication attempts, therefore, to offer some guidance for the future research programs aimed to unveil the molecular mechanisms underlying the ZIKV infectivity and to develop therapeutics capable of decreasing the devastating consequences caused by ZIKV outbreak in the Americas.